Management of Duodenal Atresia in the setting of Congenital Leukemia with Massive Hepatomegaly - Sathyaprasad C Burjonrappa (EL-Med-Pub, 2013)
Down's syndrome (DS) is associated with duodenal atresia (DA) in about 8-10% of cases. Transient Myeloproliferative Disorder (TMD)/Acute Myeloid Leukemia (AML) is also associated with the trisomy 21 mutation. The occurrence of the two conditions together complicates the diagnosis and surgical management of the DA. We discuss the technical aspects of management of the DA in this clinical setting.